Hubungan peran ayah dan dukungan sosial teman sebaya dengan determinasi diri pada remaja pecandu narkoba di klinik pemulihan adiksi medan plus - Evicenna Yuris; Nefi Darmayanti; Irna Minauli (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This study aims to determine the relationship of the role of fathers with self-determination, the relationship of peer social support with self-determination, and the relationship between the role of fathers and peer social support with self-determination in adolescent drug addicts. The population in this study were adolescent drug addicts in Medan Plus Addiction Recovery Clinic. A sample of 54 teenagers were taken by purposive sampling technique. The instrument used was a scale of self-determination, the scale of the role of fathers and the scale of peer social support. The results of multiple regression analysis showed a Freg value of 11,071 with p = 0,000 (p 0,005), which indicated that there was a significant relationship between self-determination and the role of fathers with peer social support. Partially, there is a relationship between self-determination with the role of father rxy = 0.543 with p 0.01, and there is a relationship between social support of peers with self-determination rxy = 0.384 with p 0.01. R2 value of 0.303 means the role of fathers and social support of peers together make an effective contribution of 30.3% of self-determination.